2014
DOI: 10.1016/j.actamat.2014.01.039
|View full text |Cite
|
Sign up to set email alerts
|

The influence of silicon in tempered martensite: Understanding the microstructure–properties relationship in 0.5–0.6wt.% C steels

Abstract: The strengthening contributions in medium-carbon tempered martensite are unveiled in this work. By using transmission electron microscopy and synchrotron radiation X-ray diffraction, the different microstructural features have been captured; these include precipitation, grain boundary, solid solution and dislocation forest strengthening. The evolution of these features was observed as a function of tempering temperature and silicon content. In trying to elucidate the nature of grain boundary strengthening, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(92 citation statements)
references
References 33 publications
5
70
0
Order By: Relevance
“…(iv) A simplified martensite morphology is considered: prismatic prior-austenite grains with hexagonal shape, packets of polygonal shape, and rectangular blocks and laths. Their depth equals to the prior-austenite grain size.Assumption (i) is consistent with the fact that the phase transformation occurs at a very high speed and the quenching rates for the conditions tested in this work are very high [25,15]; additionally, Villa et al [26] have found no effect of the cooling rate on the microstructure arrangement in a number of steels. However, other phases can be present such as thin films of retained austenite at the lath boundaries when increasing carbon content [27][28][29] or carbides at lath boundaries or their interiors.…”
Section: Microstructure Evolution Modellingsupporting
confidence: 64%
See 2 more Smart Citations
“…(iv) A simplified martensite morphology is considered: prismatic prior-austenite grains with hexagonal shape, packets of polygonal shape, and rectangular blocks and laths. Their depth equals to the prior-austenite grain size.Assumption (i) is consistent with the fact that the phase transformation occurs at a very high speed and the quenching rates for the conditions tested in this work are very high [25,15]; additionally, Villa et al [26] have found no effect of the cooling rate on the microstructure arrangement in a number of steels. However, other phases can be present such as thin films of retained austenite at the lath boundaries when increasing carbon content [27][28][29] or carbides at lath boundaries or their interiors.…”
Section: Microstructure Evolution Modellingsupporting
confidence: 64%
“…It is interesting noting that this equation is very similar to that employed by a number of authors to estimate the dislocation density in lath martensite by neutron diffraction measurements [3,25]; however, Eq. 5 successfully illustrates the link between lath size and carbon content.…”
Section: Dislocation Densitymentioning
confidence: 87%
See 1 more Smart Citation
“…It can be seen that the data from the present work are in good agreement with previous studies with similar carbon contents. It should, however, be mentioned that in addition to carbon, other alloying elements will also affect the dislocation density of martensite [9,25,28]. This is also seen in the present work where the high-Cr alloy has a slightly higher dislocation density than the low-Cr alloy in the as-quenched condition and is in agreement with our prior observations that Cr has a similar effect to C on the lath martensite microstructure [17].…”
Section: Resultssupporting
confidence: 82%
“…Therefore, it must in general undergo a tempering treatment to improve the toughness before it is put to use [1,2]. The tempering of martensite has been investigated for a long time, and the development of transition carbides and cementite as well as defect annihilation during tempering of martensitic carbon steels is well known [3][4][5][6][7][8][9][10][11][12]. However, when it comes to highly alloyed steels that are tempered at high temperatures, the literature is scarce [13][14][15].…”
Section: Introductionmentioning
confidence: 99%